Immunisation of dogs and guinea pigs against Rhipicephalus sanguineus ticks using gut extract - Szabo, MPJ; Bechara, G. H. (Elsevier B.V., 1997)
Tick-bite naive guinea pigs were inoculated three times with Rhipicephalus sanguineus gut or salivary gland extracts and saponin as adjuvant. Dogs were inoculated three times with gut extract only as this fraction induced a more efficient resistance in guinea pigs (lower tick recovery and lower engorged female weights). Freund's adjuvant and saponin were used as adjuvants for the immunisation of dogs. Freund's adjuvant was used to enhance cellular immunity. The highest level of resistance in dogs was induced by the immunisation with gut extract and Freund's adjuvant. Many female ticks from dogs immunised this way engorged fully but died prior to oviposition. Resistant guinea pigs and dogs seemed to trigger different immune mechanisms against R. sanguineus ticks as damage to parasites also differed. A major role for cellular immunity in the resistance of dogs against R. sanguineus ticks is suggested. Resistance mechanisms against R. sanguineus ticks is discussed.
Keywords: immunisation; gut extract; Freund's adjuvant; saponin; dog; Guinea pig; Rhipicephalus sanguineus